2022
DOI: 10.3390/jcdd9040103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Management of Methicillin-Resistant Staphylococcus aureus Pericarditis—Systematic Review

Abstract: In the expanding era of antibiotic resistance, new strains of Staphylococcus aureus have emerged which possess resistance to traditionally used antibiotics (MRSA). Our review aimed to systematically synthesize information on previously described MRSA pericarditis cases. The only criterion for inclusion was the isolation of MRSA from the pericardial space. Our review included 30 adult and 9 pediatric patients (aged: 7 months to 78 years). Comorbid conditions were seen in most adult patients, whereas no comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Influenza infections also predispose patients to a secondary bacterial infection, most commonly pneumonia. The pericardium may also be affected, with rare case reports of Methicillin-resistant Staphylococcus Aureus (MRSA), Group A Streptococcus , and Streptococcus pneumoniae pericarditis [ 103 , 104 , 105 , 106 ]. This occurs due to multiple immunological mechanisms, including damage of the tracheobronchial epithelial layer and local immunologic response suppression (i.e., bacterial clearance), causing easier bacterial adherence and translocation [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza infections also predispose patients to a secondary bacterial infection, most commonly pneumonia. The pericardium may also be affected, with rare case reports of Methicillin-resistant Staphylococcus Aureus (MRSA), Group A Streptococcus , and Streptococcus pneumoniae pericarditis [ 103 , 104 , 105 , 106 ]. This occurs due to multiple immunological mechanisms, including damage of the tracheobronchial epithelial layer and local immunologic response suppression (i.e., bacterial clearance), causing easier bacterial adherence and translocation [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of MRSA pericarditis case reports found vancomycin alone or in-combination with other anti-staphylococcal agents was effective in approximately 60% of patients. 3 We report the first case describing the use of AUC/MIC vancomycin dosing and subsequent use of combination salvage therapy in an adult patient with MRSA purulent pericarditis.…”
Section: Discussionmentioning
confidence: 99%
“…However, early diagnosis and treatment of purulent pericarditis from MRSA with sufficient source control are critical because of the downstream complications of pericardial tamponade, septic shock, pericardial abscess formation, and constrictive pericarditis [ 10 ]. With greater than one-third of patients with purulent pericarditis secondary to MRSA initially presenting with a lack of bacteremia and a high risk of pericardial injury in the setting of uremia, identification of the etiology can be difficult, but pericardial drainage and source control is critical to avoid the aforementioned complications due to delay in intervention [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for cases of purulent pericarditis from MRSA, hematogenous spread has been the most commonly cited means of seeding the pericardium with only a few cases reporting osteomyelitis as a documented source [ 17 , 18 ]. An expedited TTE with pericardiocentesis should be done for any clinical suspicion for an enlarging pericardial effusion because of the high prevalence of cardiac tamponade (84%) noted in a recent systematic review [ 14 ]. Cultures from the pericardial fluid should be sent for bacterial, fungal, and tuberculosis studies to confirm the diagnosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation